A study on the reliability and validity of the Korean version of the parenting outcome expectancy scale for parents of elementary school students - Kim, Yoonjung; Lee, Jungmin; Ross, Ratchneewan (Frontiers in Psychology, 2023)
Many parents do not engage in active discussions with their children about sexuality. This can contribute to negative sexual and reproductive health outcomes among youth. To foster a healthy environment for sexual activity, it is crucial for parents to provide comprehensive sex education to their children at home. This study aimed to cross-culturally adapt and evaluate the psychometric properties of a Korean version of the Parenting Outcome Expectancy Scale to measure the sexual communication abilities of parents of elementary school students in South Korea. The study confirmed the reliability and validity of the scale, comprising five factors and 22 items, for the evaluation of the outcome expectancy of communication about sex between parents and their children. Results also demonstrated that talking about sex is still a challenge for many parents. This instrument thus can help parents prepare for sex communication with their children and for sexual education, potentially yielding a positive effect on children’s sexual health and parental satisfaction.